The complete mitogenome of Saccharina cultivar 'Haiyi No.1' (Saccharina japonica × latissima) and the phylogenetic analysis. Issue 1 (2nd January 2020) - Liu, Pengjun; Zhang, Jing
Abstract: Here, we reported the complete mitogenome of Saccharina cultivar 'Haiyi No.1' ( Saccharina japonica × latissima ). This mitogenome had a circular mapping organization with the length of 37, 657 bp and contained 66 genes including 35 protein-encoding genes, 3 rRNAs, 25 tRNAs, and 3 open reading frames (ORFs). The AT content accounted for 64.7% of the entire mitogenome. The gene content and gene order were consistent with those reported Saccharina species and cultivars. Phylogenetic analysis showed the phylogenetic relationship among Chinese Saccharina cultivars and demonstrated that 'Haiyi No.1' had a closer relationship with Pingbancai which strongly supported its genetic source.